Studi Awal: Desain Jejaring Kawasan Konservasi Perairan di Pantai Barat Sulawesi Selatan - Ahmad Faizal; Chair Rani; Farid Samawi; Hamzah Hamzah (Hasanuddin University, 2016)
This study was related to government policies , especially PP No 60 / 2007 article 19 of the mandate of the establishment of network of marine conservation areas in various levels, both local ( provincial ), national, regional and global. One aspect is the establishment of a network of ecological data availability . The method used is the spatial analysis techniques combined with field surveys in the waters of the West Coast of South Sulawesi , especially in the waters of Makassar . Research shows that the condition of each ecosystem ; seagrass with range from 32.5 to 72.5 % with an average of 54 % (Good Condition) condition of coral reef ecosystems which range covered of 17.5 to 57.5 % with an average of 39.5 , % (critical condition ) and condition of mangrove ecosystem with moderate conditions with an area 142 hectares which in the category of dence